(untitled) (Rudarsko-geološko-naftni zbornik, 2017)
Large scale development of tight oil resources in US started after 2010. with following five-year period of favorable steady increase in crude oil price. During this relatively short expansion cycle, operating and capital expenses changed drastically for main tight oil plays due to technological improvements in both well drilling and completion, expansion of service sector as well as loose government monetary policy which allowed favorable financing. This paper analyzed trends in costs during expansion period, as well as correlation of oil price to number of operating rigs and production quotas. After 2008/2009. world financial crisis economy recovery in US was somewhat sluggish and it caused extreme volatile environment in both equity and commodity markets. In such volatile environment intra-day crude oil prices, as well as other commodities and equities, show significant reaction to monthly published macroeconomic indicator reports, which give better overviews of trends in economic recovery. Prior to announcement, these reports always have forecasted value determined by consensus among market analysts. Therefore, any positive or negative surprise in real value tends to influence price of oil. This paper investigated influence of such macroeconomic reports to closing intraday oil price, as well as effect of other important daily market indices. Analysis showed that only Producer Price Index (PPI), among other indicators, has statistical significance of affecting intraday closing oil price.